Data and Artificial Intelligence: Opportunities and Threats in Electrophysiology. Issue 3 (2020) - Leur, Rutger R van de; Boonstra, Machteld J; Bagheri, Ayoub; Roudijk, Rob W; Sammani, Arjan; Doevendans, Pieter AFM; Harst, Pim van der; Dam, Peter M van; Hassink, Ritger J; Es, Rene van; Asselbergs, Folkert W
No abstract available